Development and challenge of advanced nonaqueous sodium ion batteries. Issue 2 (May 2020) - Sun, Yi; Shi, Pengcheng; Chen, Jingjuan; Wu, Qiujie; Liang, Xin; Rui, Xianhong; Xiang, Hongfa; Yu, Yan
Highlights: The development of electrode materials and electrolyte in SIBs are summarized and discussed and the recent advances are emphasized. Several promising cathode and anode materials are highlighted for practical high-energy or high-power SIBs application, as well as the electrolytes. The perspectives and crucial challenges for advanced nonaqueous SIBs are proposed. Abstract: Room-temperature nonaqueous rechargeable sodium ion batteries (SIBs) were first studied in 1980s, which had undergone rapid revival since 2010 and could be considered as the most promising candidate for alternative to lithium ion batteries (LIBs) because of their similar chemistry and the abundant sodium reserves. Extensive efforts have been devoted in the last decade to the development of advanced SIBs including cathodes, anodes, electrolytes, as well as electrode/electrolyte interphases. Nowadays the development of SIBs comes at a critical period. Considerable encouraging works have been reported, however, several challenges still hinder their practical applications. In this review, we summarize and discuss the current progress on electrode materials and electrolytes for SIBs. To push forward their practical applications, several promising materials as well as the electrolytes are highlighted. At the end of this review, the crucial challenges and perspectives for advanced nonaqueous SIBs are also proposed. Graphical abstract: Image, graphical abstract